TGFB3-AS1 promotes Hcy-induced inflammationof macrophages via inhibiting the maturityof miR-144 and upregulating Rap1a - Hui Zhang; Yinju Hao; Anning Yang; Lin Xie; Ning Ding; Lingbo Xu; Yanhua Wang; Yong Yang; Yongsheng Bai; Huiping Zhang; Yideng Jiang (Elsevier, 2021)
It has been demonstrated that homocysteine (Hcy) can cause inflammatory diseases. Long noncoding RNAs (lncRNA) and microRNAs (miRNAs) are involved in this biological process, but the mechanism underlying Hcy-induced inflammation remains poorly understood. Here, we found that lncRNA TGFB3-AS1 was highly expressed in macrophages treated with Hcy and the peripheral blood monocytes from cystathionine beta-synthase heterozygous knockout (CBS+/−) mice with a high-methionine diet using lncRNA microarray. In vivo and in vitro experiments further confirmed that TGFB3-AS1 accelerated Hcy-induced inflammation of macrophages through the Rap1a/wnt signaling pathway. Meanwhile, TGFB3-AS1 interacted with Rap1a and reduced degradation of Rap1a through inhibiting its ubiquitination in macrophages treated with Hcy. Rap1a mediated inflammation induced by Hcy and serves as a direct target of miR-144. Moreover, TGFB3-AS1 regulated miR-144 by binding to pri-miR-144 and inhibiting its maturation, which further regulated Rap1a expression. More importantly, we found that high expression of TGFB3-AS1 was positively correlated with the levels of Hcy and proinflammatory cytokines in serum of healthy individuals and patients with HHcy. Our study revealed a novel mechanism by which TGFB3-AS1 promoted inflammation of macrophages through inhibiting miR-144 maturation to stay miR-144 regulated inhibition of functional Rap1a expression.